Finding her Amish home [large type] - Wright, Pamela Desmond (Love inspired., 2022)
"What she wants more than anything could also be the most dangerous... After her twin sister's death, Maddie Baum flees to Wisconsin Amish country with her nephew in tow in the hopes of protecting him from his criminal father. Befriending Amish shopkeeper Abram Mueller gives her a glimpse of the happiness she's been yearning for all along. Can she find a fresh start with Abram--or will old sins tear them apart?"--Back cover.